Diagnosa Penyakit Hipertensi Menggunakan Sistem Pakar Dengan Metode Certainty Factor - Ninditama, Ilsa Palingga; Nopalia; Rizki, Fido (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2024)
Hypertension is a disease that has a high mortality rate every year and can attack individuals of all ages. Hypertension is also one of the entry points or risk factors for diseases such as heart disease, kidney failure, diabetes mellitus and stroke. The aim of this research is to be able to help the community when there are limited tools and experts which cause the community to have difficulty in diagnosing hypertension, on the other hand there are also people who have limited time or money to diagnose hypertension at health facilities such as Community Health Centers, Homes. Hospitals, Clinics and other health facilities. The system development method used in this research is the waterfall method, the waterfall method is a system development method that provides systematic and sequential approaches to software development such as requirements specifications, software design implementation, testing and so on, as for the stages in The waterfall system development method starts from analysis, design, coding and testing. The expert system used in this research uses a certainty factor in diagnosing the percentage of hypertension. The certainty factor method is a method for proving the uncertainty of an expert's thinking, where to accommodate this one usually uses a certainty factor to describe the expert's level of confidence in The problem being faced. The results of this research have a contribution, namely that the application of this expert system can quickly and precisely diagnose whether someone is suffering from hypertension or not based on the data set that has been compiled.